Central core disease mutations R4892W, I4897T and G4898E in the ryanodine receptor isoform 1 reduce the Ca(2+) sensitivity and amplitude of Ca(2+)-dependent Ca(2+) release - Du, Guo Guang (Portland Press Ltd., 2004)
Three CCD (central core disease) mutants, R4892W (Arg(4892)→Trp), I4897T and G4898E, in the pore region of the skeletal-muscle Ca(2+)-release channel RyR1 (ryanodine receptor 1) were characterized using a newly developed assay that monitored Ca(2+) release in the presence of Ca(2+) uptake in microsomes isolated from HEK-293 cells (human embryonic kidney 293 cells), co-expressing each of the three mutants together with SERCA1a (sarcoplasmic/endoplasmic-reticulum Ca(2+)-ATPase 1a). Both Ca(2+) sensitivity and peak amplitude of Ca(2+) release were either absent from or sharply decreased in homotetrameric mutants. Co-expression of wild-type RyR1 with mutant RyR1 (heterotetrameric mutants) restored Ca(2+) sensitivity partially, in the ratio 1:2, or fully, in the ratio 1:1. Peak amplitude was restored only partially in the ratio 1:2 or 1:1. Reduced amplitude was not correlated with maximum Ca(2+) loading or the amount of expressed RyR1 protein. High-affinity [(3)H]ryanodine binding and caffeine-induced Ca(2+) release were also absent from the three homotetrameric mutants. These results indicate that decreased Ca(2+) sensitivity is one of the serious defects in these three excitation–contraction uncoupling CCD mutations. In CCD skeletal muscles, where a mixture of wild-type and mutant RyR1 is expressed, these defects are expected to decrease Ca(2+)-induced Ca(2+) release, as well as orthograde Ca(2+) release, in response to transverse tubular membrane depolarization.